SPECTROSCOPIC EVALUATION OF ACTIVATED CHARCOAL AS A POISON ANTIDOTE FOR GLICLAZIDE DRUG - Hassen, Jasim Hamadi; Ayfan, Abdalkareem Hamad; Farhan, Yaser Mohamad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The aim of the present study is to evaluate the ability of activated charcoal in adsorbing overdosage of gliclazide drug, and to study the effects of pH, concentration and time on this process. Methods: To evaluate the effect of pH, concentration and time; 50 ml of the drug solution (100 mg/L) were allowed to stand with the activated charcoal for 1 h at pH of 1.5, 4, 7, and 9 for pH study. 50 ml of the drug solution concentrations of 25, 50, 75, and 100 (mg/L) were allowed to stand with 1 g activated charcoal for 1 h for concentration study. 50 mg of the drug solution (100 mg/L) were allowed to stand with the activated charcoal for 15, 30, 45, and 60 min for time study. The concentrations of the adsorbed drug were determined spectrophotometrically. Results: The adsorption of the gliclazide drug on activated charcoal was found to be pH, concentration, and time-dependent. The amounts of the drug adsorbed were 3, 0.75, 0.6, and 0.5 mg/g for pHs 1.5, 4, 7, and 9, respectively, for pH study. For concentration study, the amounts adsorbed were 0.15, 0.22, 0.33, and 0.58 mg/g for concentrations 25, 50, 75, and 100 mg/L, respectively. For time study, the amounts were 0.3, 0.4, 0.51, and 0.65 mg/g for reaction times 15, 30, 45, and 60 min, respectively. Conclusion: The best adsorption circumstances of gliclazide drug on activated charcoal that were found; acidic pH, a high concentration of the drug and longtime of contact.